„Prawo do edukacji” wobec „obowiązku edukacji” w kontekście wybranych międzynarodowych i polskich rozwiązań prawnych - Budajczak, Marek (Czasopismo Prawno-Historyczne, 2026)
This article examines two formal concepts: the ‘right to education’ and ‘compulsory education’ in international conventions (as formulated in the Universal Declaration of Human Rights [UDHR]) and in national legislation (using Poland as a broader example), respectively, to identify their degree of internal and external coherence. Some additional categories connected to these two main ones, such as compulsory school attendance, compulsory preschool attendance, and parents’ right to educate their child, are also considered. The question posed here is: who is bound by the statements of right and duty in Article 26 of the UDHR? Is it the individual, who is free and compelled to receive education, or the citizen as the holder of the right and the state as the bearer of the duty to guarantee it? The cited data demonstrate the current status of these two categories in the constitutions of different countries. Particular attention is paid to the complex Polish legislation in the field of education, from the national constitution to the relevant legal acts. Along with the presentation of issues, the article outlines possible solutions. The analytical method employed is linguistic, essentially rooted in commonsense meanings. The conclusions drawn from these comparisons, in relation to the standards of natural language logic, suggest the need to reconstruct the wording of agreements adopted by the international community and Polish legal acts.